The Man and His Social Capital (UNWE Yearbook, 2014)
In the recent decades the social capital has become one of the main focuses in the research studies on the matters of social integration. This has happened not only because of seeking to better know how the coexistence of people is functioning but also because of the necessity to find mechanisms for the stability and sustainability of that coexistence. There are two clear-cut trends in the development of the modern society that are constantly existing in a complicated relationship. The first one is aimed at building a common identity and common goals, and the second – at individuation and realization of individual life strategies. The harmonization of these two trends (which is obviously a difficult task), requires reconciliation of the purposes for which the social capital is used.Although there isn’t an agreed definition of "social capital" and despite of its transformation (in some particular cases) in a modern label of different aspects of the social, that specific capital plays an important role in integrating society and building the identity of its members. This determines the increased interest in this matter not only of the representatives of different sciences, but also of authoritative international organizations like the World Bank and Organization for Economic Cooperation and Development. The documents of the World Bank define the social capital as a network of all institutions, relationships and norms that create the quality and quantity of social interactions. In this case this is not just a mechanical aggregation of the existing institutions, relationships and norms. This is a social cooperation, a cohesion which gives people potentiality to build together their lives. Organization for Economic Cooperation and Development defines social capital as a key component to building and maintaining sociality.So, creating conditions for mobilization of social energy for achieving public goals is extremely important. Social capital should be beneficial for society, it should contribute to strong economic growth, should improve quality of life and prevent conflicts, aggression and crime. The crisis during the recent years and the deficits of institutional stability have led to the need of a more precise analysis of the way the coexistence is build, and also to a more detailed look at the capabilities of the society members to achieve their own life strategies.In this paper the author will present the outlines of her study on social capital in the traditions of sociological science, which requires: first, specific processes, relationships and activities to be distinguished from the rest of the social world and to be verbally defined (which is usually called definition); second, determining the levels at which this social phenomenon (social capital) can be identified (including specific forms of compatibility, spatial locations and subjects of its "production"); and third, the consequences of the ways it is used.